The influence of age and captivity on cardiac structure and function in rhesus macaques - T. G. Dawkins; B. A. Curry; A. Drane; V. N. Rivas; Y. Ueda; J. A. Stern; D. Philips; J. Negron-Del Valle; Lauren Brent; James Higham; Angelina Ruiz-Lambides; Noah Snyder-Mackler; et al. (GeroScience, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Effects of amount of lactose in milk replacer on gastrointestinal function of dairy calves - R. Fukumori; T. Nakayama; M. Hirose; I. Norimura; K. Izumi; K. Shimada; H. Mineo; M.A. Steele; S. Gondaira; H. Higuchi; T. Watanabe; H. Ueda; et al. (Animal Feed Science and Technology, 2025)

Activation of α7 nicotinic acetylcholine receptor augments nerve growth factor action on PCtrk cells - T. Mutoh; Y. Niimi; Akihiro Ueda (Toxicology, 2024)

Regression and trend analysis of LEAP 2020 experimental results - Mourad Zeghal; Alejandro Sepulveda; Majid T. Manzari; Bruce Kutter; Tarek Abdoun; Stuart K. Haigh; Wen-Yi Hung; Evangelia Korre; Gopal S.P. Madabhushi; Satish Manandhar; Mitsu Okamura; Kyohei Ueda; et al. (Soil Dynamics and Earthquake Engineering, 2024)

Evaluating the effects of climate change on different stages of weathering in some granitic and granodioritic landslide prone areas of Japan - Md. Hasan Imam; Chiaki T. Oguchi; Tsuyoshi Wakatsuki; Mariko Ueda (Modeling Earth Systems and Environment, 2024)

Correlation of CPT measurements and relative density of LEAP-2017 and LEAP-2020 centrifuge models - Alejandro Sepulveda; Mourad Zeghal; Bruce L. Kutter; Majid T. Manzari; Tarek Abdoun; Sandra Escoffier; Stuart K. Haigh; Wen-Yi Hung; Evangelia Korre; Gopal S.P. Madabhushi; Satish Manandhar; Mitsu Okamura; et al. (Soil Dynamics and Earthquake Engineering, 2024)

Dietary nitrate does not acutely enhance skeletal muscle blood flow and vasodilation in the lower limbs of older adults during single-limb exercise - William E. Hughes; Nicholas T. Kruse; Kenichi Ueda; Andrew J. Feider; Satoshi Hanada; Joshua M. Bock; Darren P. Casey (European Journal of Applied Physiology, 2020)

Assessment of climate-induced degree of chemical weathering in some granite and granodiorite slopes of Japan - Md. Hasan Imam; Chiaki T. Oguchi; Tsuyoshi Wakatsuki; Mariko Ueda (Modeling Earth Systems and Environment, 2019)

Correction to: Common findings of blaCTX-M-55-encoding 104–139 kbp plasmids harbored by extended-spectrum β-lactamase-producing Escherichia coli in pork meat, wholesale market workers, and patients with urinary tract infection in Vietnam - T. A. V. Hoang; T. N. H. Nguyen; S. Ueda; Q. P. Le; T. T. N. Tran; T. N. D. Nguyen; T. V. K. Dao; M. T. Tran; T. T. T. Le; T. L. Le; T. Nakayama; I. Hirai; et al. (Current Microbiology, 2019)

Effects of Transcranial Direct Current Stimulation of the Posterior Parietal Cortex on the Control of Visual Attention - Y. Hirakawa; K. Takeda; S. Tanabe; S. Koyama; T. Ueda; K Morishima; M. Iwai; S. Kuno; I. Motoya; H. Sakurai; Y. Kanada (Neurophysiology, 2019)

Vasoconstrictor responsiveness in contracting human muscle: influence of contraction frequency, contractile work, and metabolic rate - Nicholas T. Kruse; William E. Hughes; Kenichi Ueda; Darren P. Casey (European Journal of Applied Physiology, 2017)

Dynamic reorganization of the endomembrane system during spermatogenesis in Marchantia polymorpha - Naoki Minamino; Takehiko Kanazawa; Ryuichi Nishihama; Katsuyuki T. Yamato; Kimitsune Ishizaki; Takayuki Kohchi; Akihiko Nakano; Takashi Ueda (Journal of Plant Research, 2017)

Common findings of bla CTX-M-55-encoding 104–139 kbp plasmids harbored by extended-spectrum β-lactamase-producing Escherichia coli in pork meat, wholesale market workers, and patients with urinary tract infection in Vietnam - T. A. V. Hoang; T. N. H. Nguyen; S. Ueda; Q. P. Le; T. T. N. Tran; T. N. D. Nguyen; T. V. K. Dao; M. T. Tran; T. T. T. Le; T. L. Le; T. Nakayama; I. Hirai; et al. (Current Microbiology, 2017)

Enhanced loading regimen of teicoplanin is necessary to achieve therapeutic pharmacokinetics levels for the improvement of clinical outcomes in patients with renal dysfunction - T. Ueda; Y. Takesue; K. Nakajima; K. Ichiki; A. Doita; Y. Wada; T. Tsuchida; Y. Takahashi; M. Ishihara; H. Ikeuchi; M. Uchino; T. Kimura (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Hydrogeochemistry and quality of surface water and groundwater in the vicinity of Lake Monoun, West Cameroon: approach from multivariate statistical analysis and stable isotopic characterization - Brice T. Kamtchueng; Wilson Y. Fantong; Mengnjo J. Wirmvem; Rosine E. Tiodjio; Alain F. Takounjou; Jules R. Ndam Ngoupayou; Minoru Kusakabe; Jing Zhang; Takeshi Ohba; Gregory Tanyileke; Joseph V. Hell; Akira Ueda (Environmental Monitoring and Assessment, 2016)

Biological index of environmental lead pollution: accumulation of lead in liver and kidney in mice - T. Takano; Y. Okutomi; M. Mochizuki; Y. Ochiai; F. Yamada; M. Mori; F. Ueda (Environmental Monitoring and Assessment, 2015)

Ecological differences in response of bird species to radioactivity from Chernobyl and Fukushima - A. P. Møller; T. A. Mousseau; I. Nishiumi; K. Ueda (Journal of Ornithology, 2015)

Characterization of a new anulavirus isolated from Amazon lily plants - S. Fuji; M. Kikuchi; S. Ueda; T. Toda; H. Furuya; F. Fukumoto; K. Hanada (Archives of Virology, 2013)

Exogenous ghrelin improves blood flow distribution in pulmonary hypertension—assessed using synchrotron radiation microangiography - Daryl O. Schwenke; Emily A. Gray; James T. Pearson; Takashi Sonobe; Hatsue Ishibashi-Ueda; Isabel Campillo; Kenji Kangawa; Keiji Umetani; Mikiyasu Shirai (Pflügers Archiv - European Journal of Physiology, 2011)

Reliability and Reproducibility of Vertical Diffusion Cells for Determining Release Rates from Semisolid Dosage Forms - Walter W. Hauck; Vinod P. Shah; Steven W. Shaw; Clarence T. Ueda (Pharmaceutical Research, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Relationship between eyed‐egg percentage and levels of cortisol and thyroid hormone in masu salmon Oncorhynchus masou - M. Mingist; T. Kitani; N. Koide; H. Ueda (Journal of Fish Biology, 2007)
A possible cause of the low eyed‐egg percentage that afflicts pond‐reared masu salmon Oncorhynchus masou at a fish hatchery (Kumaishi Fish Hatchery, Hokkaido, Japan) was investigated. Serum cortisol levels of masu salmon during the spawning period were compared between individuals from Kumaishi and those from another station (Mori). Cortisol, thyroxine (T 4 ) and triiodothyronine (T 3 ) hormones were also measured in eyed eggs and their levels were compared to the eyed‐egg percentage. Serum cortisol levels were significantly higher at Kumaishi than at Mori in May and July of the breeding season. At the Kumaishi station, there was a linear positive relationship between serum cortisol and fertilized‐egg cortisol levels of female masu salmon. As cortisol levels in both ovulating females and eyed eggs increased, the eyed‐egg percentage decreased, indicating a highly significant negative relationship between cortisol levels and eyed‐egg percentage. In contrast, as T 3 and T 4 levels in eyed eggs increased, the eyed‐egg percentage increased. The strong positive correlation between high cortisol levels in serum and in eyed eggs at Kumaishi indicates that the frequently higher cortisol levels may have caused the lowering of the eyed‐egg percentage.

Bovine and water buffalo Mx2 genes: polymorphism and antiviral activity - H. A. E. Babiker; Y. Nakatsu; K. Yamada; A. Yoneda; A. Takada; J. Ueda; H. Hata; T. Watanabe (Immunogenetics, 2006)

Population Research of Genetic Polymorphism at Amino Acid Position 631 in Chicken Mx Protein with Differential Antiviral Activity - T. Seyama; J. H. Ko; M. Ohe; N. Sasaoka; A. Okada; H. Gomi; A. Yoneda; J. Ueda; M. Nishibori; S. Okamoto; Y. Maeda; T. Watanabe (Biochemical Genetics, 2006)

Molecular mechanisms involved in anti-inflammatory effects of proton pump inhibitors - O. Handa; N. Yoshida; N. Fujita; Y. Tanaka; M. Ueda; T. Takagi; S. Kokura; Y. Naito; T. Okanoue; T. Yoshikawa (Inflammation Research, 2006)

Roles of Aquaporin-3 Water Channels in Volume-Regulatory Water Flow in a Human Epithelial Cell Line - H. Kida; T. Miyoshi; K. Manabe; N. Takahashi; T. Konno; S. Ueda; T. Chiba; T. Shimizu; Y. Okada; S. Morishima (The Journal of Membrane Biology, 2005)

Effects of an Environmental Estrogen on Male Gulf Pipefish, Syngnathus scovelli (Evermann and Kendall), a Male Brooding Teleost - N. Ueda; C. Partridge; J. Bolland; J. Hemming; T. Sherman; A. Boettcher (Bulletin of Environmental Contamination and Toxicology, 2005)

Complete nucleotide sequences of attenuated and severe isolates of Leek yellow stripe virus from garlic in northern Japan: Identification of three distinct virus types in garlic and leek world-wide - F. Takaki; T. Sano; K. Yamashita; T. Fujita; K. Ueda; T. Kato (Archives of Virology, 2005)

Heme oxygenase-1 inhibits cigarette smoke-induced increase in the tracheal mucosal permeability in guinea pigs in vivo - A. Tagawa; T. Kaneko; T. Shinohara; A. Ueda; T. Sato; Y. Ishigatsubo (Inflammation Research, 2005)

A novel antipsychotic, perospirone, has antiserotonergic and antidopaminergic effects in human brain: findings from neuroendocrine challenge tests - M. Iwakawa; T. Terao; A. Soya; H. Kojima; Y. Inoue; N. Ueda; R. Yoshimura; J. Nakamura (Psychopharmacology, 2004)

Elimination of chrysanthemum stunt viroid from an infected chrysanthemum cultivar by shoot regeneration from a leaf primordium-free shoot apical meristem dome attached to a root tip - M. Hosokawa; A. Otake; K. Ohishi; E. Ueda; T. Hayashi; S. Yazawa (Plant Cell Reports, 2004)

Delimitation of the chromosomal region for a quantitative trait locus, qUVR-10, conferring resistance to ultraviolet-B radiation in rice (Oryza sativa L.) - T. Ueda; T. Sato; H. Numa; M. Yano (Theoretical and Applied Genetics, 2004)

Comparative analyses of serum vitellogenin levels in male and female Reeves' pond turtles ( Chinemys reevesii ) by an immunological assay - Y. Ueda; H. Hoshi; T. Uemura; Y. Kamata; N. Tada; M. Saka (Journal of Comparative Physiology B, 2004)

Mapping of quantitative trait loci associated with ultraviolet-B resistance in rice (Oryza sativa L.) - T. Sato; T. Ueda; Y. Fukuta; T. Kumagai; M. Yano (Theoretical and Applied Genetics, 2003)

FISH-Mapping of 18S Ribosomal RNA Genes and Telomeric Sequences in the Japanese Bitterlings Rhodeus ocellatus kurumeus and Tanakia limbata (Pisces, Cyprinidae) Reveals Significant Cytogenetic Differences in Morphologically Similar Karyotypes - L. Sola; E. Gornung; H. Naoi; R. Gunji; C. Sato; K. Kawamura; R. Arai; T. Ueda (Genetica, 2003)

Application of odor-stimulated labeling methods of olfactory receptor neurons of sockeye salmon using agmatine - H. Iwase; S. Matsumoto; T. Shoji; H. Ueda (Fish Physiology and Biochemistry, 2003)

Changes in GnRH levels in the brain and pituitary gland during migrations of sockeye salmon and chum salmon - T. Kitani; S. Matsumoto; H. Yamada; M. Amano; M. Iwata; H. Ueda (Fish Physiology and Biochemistry, 2003)

Amino acids in stream water are essential for salmon homing migration - T. Shoji; Y. Yamamoto; D. Nishikawa; K. Kurihara; H. Ueda (Fish Physiology and Biochemistry, 2003)

Detection of Japanese yam mosaic virus by RT-LAMP - S. Fukuta; T. Iida; Y. Mizukami; A. Ishida; J. Ueda; M. Kanbe; Y. Ishimoto (Archives of Virology, 2003)

Chloroplast DNA phylogeography of Fagus crenata (Fagaceae) in Japan - N. Fujii; N. Tomaru; K. Okuyama; T. Koike; T. Mikami; K. Ueda (Plant Systematics and Evolution, 2002)

Analysis of salt-inducible genes in barley roots by differential display - A. Ueda; W. Shi; T. Nakamura; T. Takabe (Journal of Plant Research, 2002)

Renal damage and salt-dependent hypertension in aged transgenic mice overexpressing endothelin-1 - T. Shindo; H. Kurihara; K. Maemura; Y. Kurihara; O. Ueda; H. Suzuki; T. Kuwaki; K.-H. Ju; Y. Wang; A. Ebihara; H. Nishimatsu; N. Moriyama; et al. (Journal of Molecular Medicine, 2002)

Distribution of CH 4 in the north basin of Lake Biwa and tributary rivers - Y. Yamada; T. Koitabashi; T. Ueda; E. Wada (Limnology, 2001)

Metabolism of 2-Nitrofluorene, an Environmental Pollutant, and 2-Acetylaminofluorene in Fish - O. Ueda; S. Kitamura; Y. Huruse; T. Saito; Y. Kanzaki; Y. Yano; K. Tatsumi; S. Ohta (Bulletin of Environmental Contamination and Toxicology, 2001)

Flexibility on the karyotype evolution in bitterlings (Pisces, Cyprinidae) - T. Ueda; H. Naoi; R. Arai (Genetica, 2001)

Investigation of physicochemical form of uranium in sediment of brackish Lake Obuchi using sequential extraction procedure - S. Ueda; H. Hasegawa; T. Iyogi; H. Kawabata; K. Kondo (Limnology, 2000)

Microtubule-dependent migration of the cell nucleus toward a future leading edge in amoebae ofPhysarum polycephalum - M. Ueda; T. Kuroiwa; S. Matsunaga; S. Ogihara (Protoplasma, 2000)

Direct transformation and plant regeneration of the haploid liverwort Marchantia polymorpha L. - Mizuki Takenaka; Shohei Yamaoka; Tsutomu Hanajiri; Yuu Shimizu-Ueda; Katsuyuki T. Yamato; Hideya Fukuzawa; Kanji Ohyama (Transgenic Research, 2000)

Polychlorinated Dibenzo- p -Dioxins (PCDDs), Dibenzofurans (PCDFs), Biphenyls (PCBs), and Organochlorine Pesticides in Yellow-Blotched Map Turtle from the Pascagoula River Basin, Mississippi, USA - K. Kannan; M. Ueda; J. A. Shelby; M. T. Mendonca; M. Kawano; M. Matsuda; T. Wakimoto; J. P. Giesy (Archives of Environmental Contamination and Toxicology, 2000)

Interannual, seasonal, local and body size variations in reproduction of the prawn Penaeus ( Marsupenaeus ) japonicus (Crustacea: Decapoda: Penaeidae) in the Ariake Sea and Tachibana Bay, Japan - M. Minagawa; S. Yasumoto; T. Ariyoshi; T. Umemoto; T. Ueda (Marine Biology, 2000)

Rearrangement of cortical microtubules from transverse to oblique or longitudinal in living cells of transgenicArabidopsis thaliana - K. Ueda; T. Matsuyama (Protoplasma, 2000)

Human cytotoxic T-lymphocyte responses specific for peptides of the wild-type Wilms' tumor gene ( WT1 ) product - Y. Oka; O. A. Elisseeva; A. Tsuboi; H. Ogawa; H. Tamaki; H. Li; Y. Oji; E. H. Kim; T. Soma; M. Asada; K. Ueda; E. Maruya; et al. (Immunogenetics, 2000)

Analysis of mitochondrial DNA of an endangered beech species, Fagus hayatae Palibin ex Hayata - Sumie Kato; Takayoshi Koike; Thomas T. Lei; Chang-Fu Hsieh; Kunihiko Ueda; Tetsuo Mikami (New Forests, 2000)

”In vivo cryotechnique" in combination with replica immunoelectron microscopy for caveolin in smooth muscle cells - I. Takayama; N. Terada; T. Baba; H. Ueda; Y. Kato; Y. Fujii; S. Ohno (Histochemistry and Cell Biology, 1999)

Allelic diversity at class II DRB1 and DQB loci of the pig MHC ( SLA ) - T. Hosokawa Kanai; Y. Tanioka; M. Tanigawa; Y. Matsumoto; S. Ueda; T. Onodera; Y. Matsumoto (Immunogenetics, 1999)

Analysis of 5′-upstream non-coding region of FI-carboxymethyl cellulase gene from Aspergillus aculeatus - T. Ooi; K. Morotomi; S. Kinoshita; J. Honda; S. Ueda; M. Arai (Biotechnology Letters, 1999)

Geographical variations in the trophic structure of the plankton community along a eutrophic–mesotrophic–oligotrophic transect - S. Uye; N. Iwamoto; T. Ueda; H. Tamaki; K. Nakahira (Fisheries Oceanography, 1999)
The geographical variations in trophic structure of the plankton community, as defined by total and relative carbon biomass of phytoplankton (PP), bacteria (BA), heterotrophic nanoflagellates (HNF), microzooplankton (MZ), and herbivorous (HNZ) and carnivorous net‐zooplankton (CNZ), were investigated along an inshore–offshore transect from the innermost part of Osaka Bay to the Pacific Ocean off Kii Channel, Japan, in June 1991. Based on physico‐chemical properties of the water and topographical features, the transect was divided into three trophic areas, i.e. eutrophic, mesotrophic and oligotrophic ones. The average carbon biomass of the total plankton community was highest (438 mg m −3 ) in the inshore eutrophic area, and declined steeply offshore (141 and 26.6 mg m −3 in the mesotrophic and oligotrophic areas, respectively). In the offshore oligotrophic area, the relative biomass of BA to PP and the relative biomass of small heterotrophs (i.e. BA, HNF and MZ) to the total heterotrophs were higher than in the other areas, indicating that the microbial food chain predominated. In the mesotrophic area, the biomass of HNZ (primarily copepods) was conspicuously high, even higher than that of PP, suggesting that the traditional grazing food chain prevailed. Because of this short food chain, a productive fishing ground is formed there. In the eutrophic area, the biomass of HNZ was much smaller relative to the enormous biomass of PP, indicating that a considerable amount of primary production was not utilized directly by the metazoan zooplankton. However, the relative contribution of the small heterotrophs to the total heterotrophs’ biomass was higher in this area, as in the oligotrophic area.

Detailed Distribution of Accelerating Foreshocks before a M 5.1 Earthquake in Japan - K. Yamaoka; T. Ooida; Y. Ueda (Pure and Applied Geophysics, 1999)

Spermatozoa in triploids of the rosy bitterling Rhodeus ocellatus ocellatus - K. Kawamura; T. Ueda; K. Aoki; K. Hosoya (Journal of Fish Biology, 1999)
Artificially induced triploid male Rhodeus ocellatus ocellatus showed typical nuptial colorations, irrespective of spermiation. In milt from triploids, abnormal spermatozoa (malformation of the head and mitochondrion, excessive formation of the head, mitochondrion and flagellum, and no flagellum) occurred at 78°4% frequency. Spermatozoa with multiflagella were most common, often with a saccate‐like organ. Many triploid spermatozoa moved actively as long as those of diploids (10·92±0·91 min=mean±S.D., P >0·05), but did not advance like diploids, spinning around until movement ceased. The sperm density in triploids was P P =0·002). In the fertilization test using the eggs of diploids ( n =1500, 30 trials), only one egg developed. The embryo chromosome number was 60 (2·5 n) and the ploidy of spermatozoa contributing to fertilization appears to be 1·5 n. The extremely low fertility of triploid R. o. ocellatus spermatozoa seems to be caused by the reduced motility and large head size of spermatozoa, and the low sperm density of the milt. The ploidy of spermatozoa that are successful in fertilization is likely to be related to the distribution pattern in the DNA content of cells.

Visualization of microtubules in living cells of transgenicArabidopsis thaliana - K. Ueda; T. Matsuyama; T. Hashimoto (Protoplasma, 1999)

The biological roles of small GTPases and interacting proteins in plants - Hirofumi Uchimiya; Toyoaki Anai; Evalour T. Aspuria; Minami Matsui; Akihiko Nakano; Takashi Ueda (Journal of Plant Research, 1998)

Slight difference in primary amino acid sequence of p17 matrix protein of HIV-1 exerts profound influence on its antigenicity - K. Taniguchi; H. Tsuchie; S. Kageyama; M. Iwasaki; T. Takagi; F. Sasao; S. Ueda; T. Kurimura (Archives of Virology, 1998)

Correlation among dominance status, metabolic rate and otolith size in masu salmon - T. Yamamoto; H. Ueda; S. Higashi (Journal of Fish Biology, 1998)
In spatial competition between individuals, neither fish sex nor body mass affected dominance status in masu salmon Oncorhynchus masou . In contrast, resting metabolic rate ( M R ) was significantly correlated with dominance status, indicating that a high metabolic rate can increase the dominance rank of juvenile salmon. Whole animal growth rate was significantly correlated with M R , but not with initial body weight. This suggests that the body size of masu salmon is not a cause, but rather a consequence, of dominance status which is closely related to M R . The increment width between otolith daily rings was also significantly correlated with M R . Thus, the size of the Otolith may indicate the degree of M R .

Effects of Low and High Density Lipoproteins on Renal Cyclosporine A and Cyclosporine G Disposition in the Isolated Perfused Rat Kidney - Michelle L. Strong; Clarence T. Ueda (Pharmaceutical Research, 1997)

Genomic organization and chromosomal localization of the human casein gene family - Y. Fujiwara; M. Miwa; M. Nogami; K. Okumura; T. Nobori; T. Suzuki; M. Ueda (Human Genetics, 1997)

Naturally occurring dual infection with human and bovine rotaviruses as suggested by the recovery of G1P8 and G1P5 rotaviruses from a single patient - O. Nakagomi; Y. Isegawa; R. L. Ward; D. R. Knowlton; E. Kaga; T. Nakagomi; S. Ueda (Archives of Virology, 1994)

Provocation of respiratory allergy in guinea pigs following inhalation of free toluene diisocyanate - K. Aoyama; J. Huang; A. Ueda; T. Matsushita (Archives of Environmental Contamination and Toxicology, 1994)

Rapid detection of African horsesickness virus by the reverse transcriptase polymerase chain reaction (RT-PCR) using the amplimer for segment 3 (VP3 gene) - K. Sakamoto; R. Punyahotra; N. Mizukoshi; S. Ueda; H. Imagawa; T. Sugiura; M. Kamada; A. Fukusho (Archives of Virology, 1994)

Generation and characterization of the human immunodeficiency virus type 1 mutants - A. Adachi; N. Ono; H. Sakai; K. Ogawa; R. Shibata; T. Kiyomasu; H. Masuike; S. Ueda (Archives of Virology, 1991)

Polypeptide analysis with monoclonal antibodies of A type inclusion bodies induced by cowpox virus - N. Kitamoto; S. Tanimoto; K. Hiroi; T. Tanaka; H. Miyamoto; N. Wakamiya; K. Ikuta; S. Ueda; S. Kato (Archives of Virology, 1986)

Cross-reactivity between cowpox and vaccinia viruses with monoclonal antibodies - N. Kitamoto; E. Goto; S. Tanimoto; T. Tanaka; H. Miyamoto; N. Wakamiya; K. Ikuta; S. Ueda; S. Kato (Archives of Virology, 1984)

Structure-biodegradability relationships in pyrethroid insecticides - John E. Casida; Kenzo Ueda; Loretta C. Gaughan; Lien T. Jao; David M. Soderlund (Archives of Environmental Contamination and Toxicology, 1975)